1987
DOI: 10.1111/j.1439-0418.1987.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the entomofauna of cones of Abies alba Mill. in the Roztocze National Park in Poland

Abstract: A total of 23,319 individuals representing 26 insect species were obtained from 1,063 cones of Abies alba Mill. in 1982–1986. This material originated from the Roztocze National Park in Poland where the natural range of European fir reaches its north eastern boundary. The coenotic groups of insects have been given and the indexes of domination (D), stability of incidences (C), species diversity (d), and Agrell's index of species co‐existence (Ag) have been calculated. Zusammenfassung Erste Untersuchungen über … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Studies carried out in the Tatra National Park showed that between 1982 and 1986, the overall damage caused by R. piceae and M. suspectus amounted to 13.0 % and 0.1 % respectively ( Skrzypczyńska , 1988). In the Roztocze National Park, however, during the same period of time, E. impossibile was the most important pest of A. alba cones, representing 37.4 % of all pests encountered ( Skrzypczyńska et al., 1987). Similarly, E. impossibile represented 42.2 % of the A. alba cone entomofauna obtained from samples collected in the St. Cross Mountains National Park between 1987 and 1992 ( Bąk , 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in the Tatra National Park showed that between 1982 and 1986, the overall damage caused by R. piceae and M. suspectus amounted to 13.0 % and 0.1 % respectively ( Skrzypczyńska , 1988). In the Roztocze National Park, however, during the same period of time, E. impossibile was the most important pest of A. alba cones, representing 37.4 % of all pests encountered ( Skrzypczyńska et al., 1987). Similarly, E. impossibile represented 42.2 % of the A. alba cone entomofauna obtained from samples collected in the St. Cross Mountains National Park between 1987 and 1992 ( Bąk , 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The information on morphology of this species was given by SEITNER (1916), ESCHERICH (1939), KAPUSCINSKI (1966), BOUCEK (1970), NIKOL'SKAJA and ZEROVA ( ), STADNICKIJ et al (1978, SKRZYPCZYNSKA (1978a, 1988b), SCHWENKE (1982, ROQLJES (1983ROQLJES ( , 1988b) and others. The information of its biology was reported by KOZIKOWSKI and KUNTZE (1936), ESCHERICH (1939), CERMAK (1952), KAPUSCINSKI (1966), STADNICKIJ et al (1978, SKRZYPCZYNSKA (1978aSKRZYPCZYNSKA ( , 1984aSKRZYPCZYNSKA ( , 1987 (1943), ESCHERICH (1942), GYORFI (1956), KAPUSCI~~SKI (1966), STADNICKIJ et al (1978, SKRZYPCZYNSKA (1988b), SKRZYPCZYNSKA et al (1988).…”
Section: Introductionmentioning
confidence: 94%